fbpx

Solution: Solve the equations by Cramer’s Rule: 2x–y+3z=-3,3x+3y–z=10,-x–y+z=-4

(Last Updated On: March 18, 2019)

Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4.

Problem Statement: EE Board April 1997

Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4.

Problem Answer:

The value of x, y and z is equivalent to (1, 2, -1).

View Solution:
Solution: Solve the equations by Cramer’s Rule: 2x–y+3z=-3,3x+3y–z=10,-x–y+z=-4

Latest Problem Solving in Advanced Engineering Mathematics

More Questions in: Advanced Engineering Mathematics

Online Questions and Answers in Advanced Engineering Math

Solution: Solve the equations by Cramer’s Rule: 2x–y+3z=-3,3x+3y–z=10,-x–y+z=-4
5 (100%) 1 vote[s]

Add Comment

© 2014 PinoyBIX Engineering. © 2019 All Rights Reserved | How to Donate? | Follow me on Blogarama DMCA.com Protection Status
mcq in computer fundamentals
➡️ MCQ in Computer Fundamentals Series | ECE Board Exam
mcq in industrial electronics
➡️ MCQ in Industrial Electronics Series | ECE Board Exam
MCQ in Power Generators (Cells and Batteries) Part 5 | ECE Board Exam
➡️ MCQ in Power Generators, Sources, Principles, Applications Series | ECE Board Exam
mcq in electrical circuit
➡️ MCQ in Electrical Circuit Series | ECE Board Exam

NEED SUPPORT: LIKE MY PAGE & SHARE